Agile HR for Digital Transformation: Bibliometric Analysis & Overlay Visualization - Loso Judijanto; Urnika Mudhifatul Jannah (Westscience Press, 2025)
This study investigates the intellectual and collaborative landscape of research on Agile Human Resource Management (Agile HR) in the context of digital transformation. Using a bibliometric approach, data were retrieved from the Scopus database and analyzed with VOSviewer to generate co-authorship, co-citation, and keyword co-occurrence networks, as well as overlay and density visualizations. The results show that the field is organized around two tightly connected cores (digital transformation and human resource management) surrounded by clusters related to advanced digital technologies (artificial intelligence, big data, internet of things), agile and lean systems, and organizational culture. Collaboration maps reveal that a relatively small set of authors, institutions, and countries, particularly in North America, Europe, and China, dominate knowledge production, while emerging economies are gradually integrating into these networks. Overlay and density visualizations indicate a shift over time from early work on culture, risk, and project management to more recent emphasis on data-driven technologies and agile production systems, suggesting that Agile HR is increasingly conceptualized as a socio-technical capability that links people, processes, and digital tools. The study provides a structured baseline for understanding how this domain has evolved, identifies research hotspots and gaps, and outlines avenues for future inquiry into the design and implementation of Agile HR in diverse digital transformation contexts.